MANAGEMENT OF ENDOCRINE DISEASE: Male osteoporosis: diagnosis and management - should the treatment and the target be the same as for female osteoporosis?. Issue 3 (September 2020) - Porcelli, Teresa; Maffezzoni, Filippo; Pezzaioli, Letizia Chiara; Delbarba, Andrea; Cappelli, Carlo; Ferlin, Alberto
Abstract : Male osteoporosis has been neglected for too long time and there is need for a change. This condition is clearly under-estimated, under-diagnosed and under-treated. The diagnosis is often made late in the natural history of the pathology or even after a fracture event. Guidelines on screening politics do not agree whether and when men should be considered, and clinical trials are far less performed in men with respect to women. Actually, most of our knowledge on male osteoporosis, especially regarding treatment, is extrapolate from the female counterpart. Male osteoporosis is frequently secondary to other conditions and often associated with comorbidities. Therefore, identification of specific causes of male osteoporosis is essential to drive a correct and personalized treatment. Moreover, men have more osteoporosis-related complications and higher mortality rate associated with fractures. Furthermore, not only fewer men receive a correct and timely diagnosis, but also fewer men receive adequate treatment, and adherence to therapy is far less in men than in women. Of note, very few studies assessed the effect of antiosteoporotic treatments in men and most of them considered only bone density as primary endpoint. This review focuses on the areas that are still nebulous in male osteoporosis field, from identification of subjects who need to be evaluated for osteoporosis and screening programs dealing with primary prevention to diagnostic procedures for good estimates of bone quantity and quality and precise calculation of fracture risk and personalized treatment that take into account the pathophysiology of osteoporosis.